ANALISA KANDUNGAN NATRIUM BENZOAT, SIKLAMAT PADA SELAI ROTI YANG BERMEREK DAN TIDAK BERMEREK SERTA TINGKAT PENGETAHUAN PENJUAL DI PASAR PETISAH KOTA MEDAN TAHUN 2013 - dewi ayu setiawati; nurmaini *; indra chahaya (Lingkungan dan Kesehatan Kerja, 2014)
ABSTRACT Jam is one kind of food with a sweet taste, having the interesting color and most favorite by various of society. In the process of producing manufactures frequently use the preservative and the artificial sweetener to reduce the cost of production. sodium benzoate and cyclamate is one of extra material food that is not always safe if it is used over. The purpose of the research purposes is to know the type of the content on sodium benzoate and cyclamate in the branded and not branded jam as well as the seller’s knowledge level at Petisah Market, Medan in 2013. This is to see if the use of sodium benzoate and cyclamate in jam is qualified standard health. The methodsin this research is a descriptive survey. The samples were taken from Petisah Market, Medan then were examined in The Laboratory Analytical Chemistry the Faculty Of Mathematics And Natural Science University of North Sumatera. With 16 respondents by using a questionnaire as an instrument in collecting data. The results of the research 4 branded jam and 4 not branded jam is obtained all examined samples are having the content of sodium benzoate and cyclamate that does not exceed the maximum limit. The highest content of sodium benzoate on jam is 0,2876 gr/kg, and the highest content cyclamate on jam is 0,1048 gr/kg and the seller’s knowledge level categorized good with 12 respondents ( 75,0 % ). Suggested to BPOM to socialice and supervise periodically to manufacture, the seller, and consumers about to using the safe foodstuff to eat especially sodium benzoate and cyclamate. Keyword: Sodium benzoate, Cyclamate, Knowledge, Jam.